Contrasting responses of nitrogen: Phosphorus stoichiometry in plants and soils under grazing: A global meta‐analysis. Issue 5 (14th February 2021) - Yu, Rui‐Peng; Zhang, Wei‐Ping; Fornara, Dario A.; Li, Long
Abstract: Grazing by ungulate herbivores can greatly alter nitrogen ([N]) and phosphorus ([P]) concentrations in plants and soils. It is not clear, however, how grazing might affect N:P co‐limitation in grasslands depending on soil N and P availability. Here we selected 173 peer‐reviewed studies, which measured 12 key variables associated with changes in [N], [P] and N:P ratios (i.e. N:P stoichiometry) in soils and plants in the presence or absence of herbivore grazing. Subsequently, we addressed the magnitude and direction of grazing effects on these variables using a meta‐analysis approach. Grazing increased leaf [N] and [P] but decreased total and available soil [N] and [P]. Grazing also increased leaf N:P ratios while decreasing root and total soil N:P ratios. The response ratio (RR) of leaf N:P was negatively correlated with RR of plant‐available soil [P] and positively correlated with RR of available soil N:P ratio (rather than with RR of total soil N:P). Intensive grazing (e.g. heavy grazing or long‐term grazing) had in general more positive effects on plant N:P stoichiometry and negative effects on soil N:P stoichiometry than light grazing. Responses of plant‐soil N:P stoichiometry to grazing greatly varied depending on plant functional group identity, plant organizational level (i.e. species and community) and grassland type. Synthesis and applications . Our study suggests that understanding changes in available soil N:P stoichiometry (rather than total soil N:P) in response to grazing is crucial to predict nutrient co‐limitation in grassland biomes. Our findings show that P is more important for plant growth than generally thought due to greater reduction of plant‐available soil [P] under grazing. A better mechanistic understanding of the relationships between plant and available soil N:P stoichiometry under grazing will greatly help improve the sustainability of natural and semi‐natural grassland ecosystems. Abstract : Our study suggests that understanding changes in available soil N:P stoichiometry (rather than total soil N:P) in response to grazing is crucial to predict nutrient co‐limitation in grassland biomes. Our findings show that P is more important for plant growth than generally thought due to greater reduction of plant‐available soil [P] under grazing. A better mechanistic understanding of the relationships between plant and available soil N:P stoichiometry under grazing will greatly help improve the sustainability of natural and semi‐natural grassland ecosystems. 摘要: 放牧会显著改变植物和土壤的氮 (N) 磷 (P) 养分浓度, 但是尚不清楚不同放牧方式如何影响植物和土壤N:P化学计量特征 (包括氮浓度、磷浓度及N:P), 特别是还不清楚放牧条件下植物N:P化学计量特征与土壤养分有效性的关系。 本文通过整合分析的方法定量了与植物和土壤N:P化学计量特征变化相关的12个关键响应变量对放牧的响应。 放牧显著提高叶片和根系氮磷浓度, 降低了土壤氮磷浓度。同时放牧提高了叶片N:P, 但降低了根系和土壤全量N:P。 放牧条件下, 叶片N:P的提高与土壤有效磷的降低和有效N:P (有效氮: 有效磷) 的提高显著相关, 而与土壤全量氮磷浓度的变化不相关, 表明土壤有效磷的变化对植物磷吸收和叶片氮磷平衡更重要。 植物和土壤的N:P化学计量特征受放牧强度、放牧周期、放牧动物类型和草原类型等因素的调控。与短期轻度放牧相比, 长期重度放牧会加剧植物‐土壤系统的氮磷失衡。 将来的研究应更多关注放牧对土壤有效养分及N:P的影响及其与植物养分限制因子转变的关系。理解植物和土壤有效N:P在放牧利用下的变化能够对不同草原生态系统放牧管理措施的制定提供理论依据。